The population of Sanderling (Calidris alba) in 2020 Migration on the South Coast of Puger, Getem, Jember - Rohman, Abdu; Gumilang, Ragil Satriyo (Universitas Negeri Surabaya, 2021)
Sanderling (Calidris alba) is a type of shorebird that migrates from the northern hemisphere to the southern hemisphere. Indonesia is a migration route for East Asia-Australasia. The southern coastal area of the Jember Regency, one of the wetlands, especially in East Java, has become an air route and a stopover for shorebirds every year. The research objective was to determine the population of Sanderling (Calidris alba) on the southern coast of Puger and Getem, Jember Regency. Method of collecting encounter rates. Bird watching is carried out in the morning at 06.00-08.00 and in the afternoon at 15.30-17.30. Data recording includes species, number of birds, and other supporting data. Identification using the book by Mac Kinnon et al. (2010) and Bhushan, B., et al. (1993). Tools used for binocular observation, monocular, camera, and GPS. Data analysis used the density index for individual bird species using the formula method (Alikodra, 1990). The results of the study were a total of 445 individuals. Data analysis of Muara Sungai population density was the location with the four other survey locations' highest number.